Numerical Simulation of Selective Laser Melting of 304 L Stainless Steel - Jie Wu; Ju Ma; Xiaofeng Niu; Mengqing Shen; Tingting Wei; Wenqi Li (Metals, 2023)
This paper used the smoothed particle hydrodynamics (SPH) method to construct a three-dimensional mathematical model of the selective laser melting (SLM) process of 304 L austenitic stainless steel. Important driving force models for the melt pool in the SLM process were developed, including a surface tension model, a boundary normal-modified wetting effect model, a Marangoni shear force model, and a recoil pressure model. Meanwhile, the virtual particle boundary method prevented particles from flying over the solid boundary. Artificial viscosity, artificial stress, and artificial heat were added to correct the SPH equation, which provided a guarantee for the accuracy and speed of the numerical simulation of the SLM process. Finally, the temperature field and velocity field in the SLM process were explored according to the constructed mathematical model. The evolution mechanism in the melting process was analyzed, and the influence of different laser powers on the shape of the molten pool was mainly analyzed, which provided a reference for optimizing the laser parameters to reduce the surface roughness of the formed specimen.